Pelatihan Penulisan Artikel Ilmiah bagi Mahasiswa di Bandar Lampung - Fathul Mu'in; Hadi Prayitno; Rahayu Lestari; Nafrizal (Fakultas Ilmu Sosial dan ilmu Politik, 2026)
Scientific article writing is an essential academic skill for university students, yet many students still experience difficulties in developing ideas into systematic manuscripts for publication. This community service activity was conducted to improve students’ understanding and skills in writing scientific articles, particularly in formulating topics and titles, developing introductions, writing methodologies, presenting results and discussions, and composing conclusions. The activity involved sixteen students from several universities in Bandar Lampung and its surrounding areas. The method used was training and mentoring through interactive lectures, discussions, article analysis, writing practice, and writing clinic sessions. Evaluation was carried out through pre-test and post-test instruments, observation of participant involvement, and assessment of initial article drafts. The results showed a significant improvement in participants’ writing competence. The average pre-test score was 36.1 %, while the average post-test score increased to 78.7 %, indicating an improvement of 42.6 points. Participants were also able to prepare initial article drafts based on their respective topics. The main strength of this activity was the combination of conceptual explanation, direct practice, and draft mentoring, while the limitation was the relatively short duration of the training. This activity is important as an effort to strengthen academic literacy, increase students’ confidence, and encourage their readiness to participate in scientific publication.